A Cost-Effective Analysis of 3D Printing Applications in Occupational Therapy Practice - Megan Hunzeker; Rebecca Ozelie (Scholarworks @ WMU, 2021)
Background: Emerging research supports 3D printing can provide customizable, low-cost, and replicable items for application in occupational therapy, but more research is necessary to inform occupational therapists on why and how 3D printing would be applicable and feasible in practice. Method: This study is a cost-effective analysis aimed to identify practical considerations of a selection of 3D printed items in comparison to commercially available items. Ten items of adaptive equipment were downloaded from open-sourced 3D printing design websites and printed. The estimated cost of material was calculated and each print time was recorded. Items with comparable design and function were selected from a thorough internet search for analysis and comparison to the 3D printed items. Results: The results demonstrate that each 3D printed item had a positive benefit in terms of material cost and print time compared to the cost and shipping time of each comparable item. Conclusion: The 3D printed items were the more cost-effective for all items, but most significantly for niche designs with fewer available commercial alternatives. 3D printing successfully replicated commonly used adaptive equipment for a comparable cost, while allowing for customization and the ability to provide the item in-house to clients.